Peripheral ulcerative keratitis, nodular episcleritis, and pulmonary nodules as the initial signs of rheumatic arthritis: A Case Report - Wang, Jingting; Zhang, Qin; Shi, Weiyun; Pang, Yilin; Li, Suxia (Frontiers in Immunology, 2022)
Background Rheumatoid vasculitis (RV) is a rare but potentially devastating complication of rheumatoid arthritis (RA). It typically occurs in patients with extra-articular manifestations. Here we reported a case of PUK with nodular episcleritis and pulmonary nodules that occurred in the same patient without joint involvement. Case presentation A 43-year-old Chinese woman, exhibited a partial crescent-shaped marginal corneal ulcer in the right eye at admission and the ulcer developed rapidly into nearly 360-degree ulcers in both eyes within one week. Nodular episcleritis was observed in the right eye. Conjunctival biopsy revealed vasculitis. Her rheumatoid factor (RF) and anti-cyclic citrullinated protein antibody were positive, while anti-neutrophilic cytoplasmic antibody (c-ANCA) and anti-protease 3 were negative. Pulmonary nodules were found, without joint involvement. The ocular condition did not relieve under the topical and systemic use of corticosteroids, or under other immunosuppressive agents until the infliximab therapy. PUK recurrence was observed after the discontinuation of infliximab. Conclusions Rapidly deteriorated PUK with nodular episcleritis and pulmonary nodules occurred in the same patient is a special case of RA without joint involvement. This case reinforces the concept that RV may be the initial sign of RA. Infliximab can be used to prevent further progress of RA-related PUK in some refractory cases.